Containment and Suppression of Class A Fires Using CO2 Hydrate - Gaydukova O. S. Olga Sergeevna; Morozov V. Vladimir; Volkov R. S. Roman Sergeevich; Strizhak P. A. Pavel Alexandrovich (2023, 2023)
Title screen